Nucleotide binding and dimerization at the chloroplast pre-protein import receptor, atToc33, are not essential in vivo but do increase import efficiency. - Aronsson, H; Combe, J; Patel, R; Agne, B; Martin, M; Kessler, F; Jarvis, P (2010)
The atToc33 protein is one of several pre-protein import receptors in the outer envelope of Arabidopsis chloroplasts. It is a GTPase with motifs characteristic of such proteins, and its loss in the plastid protein import 1 (ppi1) mutant interferes with the import of photosynthesis-related pre-proteins, causing a chlorotic phenotype in mutant plants. To assess the significance of GTPase cycling by atToc33, we generated several atToc33 point mutants with predicted effects on GTP binding (K49R, S50N and S50N/S51N), GTP hydrolysis (G45R, G45V, Q68A and N101A), both binding and hydrolysis (G45R/K49N/S50R), and dimerization or the functional interaction between dimeric partners (R125A, R130A and R130K). First, a selection of these mutants was assessed in vitro, or in yeast, to confirm that the mutations have the desired effects: in relation to nucleotide binding and dimerization, the mutants behaved as expected. Then, activities of selected mutants were tested in vivo, by assessing for complementation of ppi1 in transgenic plants. Remarkably, all tested mutants mediated high levels of complementation: complemented plants were similar to the wild type in growth rate, chlorophyll accumulation, photosynthetic performance, and chloroplast ultrastructure. Protein import into mutant chloroplasts was also complemented to >50% of the wild-type level. Overall, the data indicate that neither nucleotide binding nor dimerization at atToc33 is essential for chloroplast import (in plants that continue to express the other TOC receptors in native form), although both processes do increase import efficiency. Absence of atToc33 GTPase activity might somehow be compensated for by that of the Toc159 receptors. However, overexpression of atToc33 (or its close relative, atToc34) in Toc159-deficient plants did not mediate complementation, indicating that the receptors do not share functional redundancy in the conventional sense.